Hubungan antara Aqidah dan Akhlak dalam Islam - Alnida Azty; Fitriah Fitriah; Lufita Sari Sitorus; Muhammad Sidik; Muhammad Arizki; Mohd. Najmi Adlani Siregar; Nur Aisyah Siregar; Rahayu Budianti; Sodri Sodri; Ira Suryani (Mahesa Research Center, 2018)
This article discusses the relationship between aqidah and morals in Islamic teachings. Aqidah as a belief system that contains the basic elements of belief, describes the source and nature of the existence of religion. Whereas morality as an ethical system describes the direction and purpose of religion. Morals in the view of Islam must rest on faith. Faith is not enough to only be kept in the heart, but it must be practiced in daily life in the form of good morals. Aqidah is closely related to morals, because morals are extracted from aqidah and emanation of themselves. Therefore if a person is a true believer, then his character will be right, good and straight. Vice versa, if aqidah is wrong, then the morals will be wrong.